Results from the Effects of MEtformin on cardiovasculaR function in AdoLescents with type 1 Diabetes (EMERALD) study: A brief report of kidney and inflammatory outcomes. Issue 3 (23rd December 2020) - Tommerdahl, Kalie L.; Bjornstad, Petter; Kendrick, Jessica; Cree‐Green, Melanie; Baumgartner, Amy D.; Pyle, Laura; Reusch, Jane E. B.; Nadeau, Kristen J.
Abstract: Youth with type 1 diabetes (T1D) demonstrate insulin resistance, independently of glycaemia, when compared to normoglycaemic peers. Insulin resistance increases the risk of cardiovascular disease and diabetic kidney disease, factors also associated with systemic inflammation. We evaluated the effect of metformin on markers of inflammation and diabetic kidney disease in adolescents with T1D. EMERALD, a double‐blind, randomized, placebo‐controlled trial of 3 months of metformin in 48 participants aged 12–21 years with T1D, included baseline and follow‐up assessments of serum creatinine and cystatin C to estimate glomerular filtration rate (eGFR), aspartate aminotransferase, alanine aminotransferase, high‐sensitivity C‐reactive protein, white blood count, platelets, adiponectin, leptin, and urine albumin: creatinine ratio (UACR). Metformin was associated with a 13.9 mL/min/1.73 m 2 (95% confidence interval 4.7–23.1 mL/min/1.73 m 2 ) increase in estimated GFR by serum creatinine versus placebo ( P ≤ 0.01), with a significant difference remaining after multivariable adjustments ( P = 0.03). Whereas eGFR measured by serum creatinine increased significantly after metformin treatment, no differences were observed in cystatin C, UACR, or systemic inflammatory markers. Additional studies with directly measured GFR in response to metformin in T1D are needed.